Development of vaccines against pertussis caused by Bordetella holmesii using a mouse intranasal challenge model. (23rd September 2016) - Saito, Momoko; Odanaka, Keita; Otsuka, Nao; Kamachi, Kazunari; Watanabe, Mineo
ABSTRACT: Bordetella holmesii is recognized as the third causative agent of pertussis (whooping cough) in addition to Bordetella pertussis and Bordetella parapertussis . Pertussis caused by B. holmesii is not rare around the world. However, to date, there is no effective vaccine against B. holmesii . We examined the protective potency of pertussis vaccines available in Japan and vaccines prepared from B. holmesii . A murine model of respiratory infection was exploited to evaluate protective potency. No Japanese commercial pertussis vaccines were effective against B. holmesii . In contrast, a wBH vaccine and an aBH vaccine prepared from B. holmesii were both protective. Passive immunization with sera from mice immunized with aBH vaccine established protection against B. holmesii, indicating that B. holmesii ‐specific serum antibodies might play an important role in protection. Immuno‐proteomic analysis with sera from mice immunized with aBH vaccine revealed that the sera recognized a BipA‐like protein of B. holmesii . An aBH vaccine prepared from a BipA‐like protein‐deficient mutant strain did not have a protective effect against B. holmesii . Taken together, our results suggest that the BipA‐like protein plays an important role in the protective efficacy of aBH vaccine.